Efficacy of statins in patients with diabetic nephropathy: a meta-analysis of randomized controlled trials. Issue 1 (December 2016) - Shen, Xue; Zhang, Zhongwen; Zhang, Xiaoqian; Zhao, Junyu; Zhou, Xiaojun; Xu, Qinglei; Shang, Hongxia; Dong, Jianjun; Liao, Lin
Abstract Background The effects of statins in patients with diabetic nephropathy are controversial. With increasing interest in the potential therapeutic role of statins in diabetic nephropathy, it is essential to evaluate its real effects. Methods PubMed, EMBASE, Web of Science databases, Cochrane Central Register of Controlled Trials and China National Knowledge Infrastructure were systematically searched for randomized controlled trials (RCTs) of statins in patients with diabetic nephropathy. Results Fourteen trials with 2866 participants were included in our meta-analysis. Compared with placebo, albuminuria and urinary albumin excretion rates in the statin group were reduced by 0.46 [95 % confidence interval (CI), −0.68 to −0.25, P < 0.0001] and 1.68 (95 % CI, −3.23 to −0.12, P = 0.03), respectively. The reduction of albuminuria was greater in patients of type 2 diabetes mellitus with diabetic nephropathy [standardized mean difference (SMD), −0.56; 95 % CI, −0.80 to −0.32, P < 0.00001] and the decrease was significant during the 1 to 3 years period of statin therapy (SMD, −0.57; 95 % CI, −0.95 to −0.19, P = 0.003). Subgroup analysis demonstrated the effects of statins were much stronger in subjects with pathologic albuminuria: change of −0.71 (95 % CI, −1.09 to −0.33, P = 0.0003) for those with urinary protein excretion 30 to 300 mg/day, −0.37 (95 % CI, −0.67 to −0.06, P = 0.02) for those with excretion more than 300 mg/day and −0.29 (95 % CI, −0.78 to 0.21, P = 0.26) for those with excretion less than 30 mg/day. In contrast, statins did not significantly reduce estimated glomerular filtration rate, serum creatinine and blood urea nitrogen levels. Conclusions Statins decrease the albuminuria and urinary albumin excretion rates significantly. The efficacy of statins on renal function is time dependent and better in type 2 diabetic patients with nephropathy.